Os microclimas do Parque Estadual de Itapuã/RS - Almeida, Alcionir Pazatto de (2020)
The aim of this thesis was to verify which local climatic factors/controls are capable of individualizing microclimates in the State Park of Itapuã/RS, an integral protection unit, located in the district of Itapuã, municipality of Viamão/RS, between the 30° 20 'S and 30° 27' S latitude coordinates, and 50º 50 'W and 51º 05' W longitude. The relationship among local climatic controls of land cover, topography, altitude, slope exposure and presence of water bodies was analyzed and also the spatio-temporal variability of air temperature and its variants and the hygrometric field in seven physiographic environments of the conservation unit from June 2017 to May 2018. The data were collected in the field, using digital thermohygrometers, installed in meteorological mini-shelters and with simultaneous measurement at all points in hourly intervals. After collection, the data were ordered and tabulated in Microsoft Excel 2010 spreadsheets and to spatialize the climatic attributes, the Surfer 8 software was used, using the Krigagem interpolation method and the ArcGis 10.2 software. There was a significant spatial-temporal variability in air temperature, relative humidity and hourly relative humidity values greater than or equal to 95% in all time scales and selected environments, with greater variation between temperatures than between hygrometric values. Among the local climate controls responsible for such variations, on a microclimate scale the water bodies Lagoa Negra and Laguna dos Patos did not influence in air temperature, however, an indirect influence of Lagoa Negra on the percentages of relative air humidity was found and in the quantitative hourly relative humidity greater than or equal to 95% in nearby areas. The research concludes that the controls exercised by the different types of land cover, water availability of the terrain, topography, altitude, slope exposure and the action of regional winds are the main responsible for the spatio-temporal variability of the atmospheric elements analyzed on a microclimate scale, whose influence modifies its values in the air layer closest to the ground, being able to generate individualized microclimates. From this relationship, it was possible to identify and propose five microclimatic units in Itapuã State Park: Beaches and Hillsides Unit, Fora Beach Unit, Bosque Pond Unit, Hill Unit and Natural fields Unit.